Phase II Clinical Trial of Neoadjuvant Alternating Doublet Chemotherapy With Ifosfamide/Doxorubicin and Etoposide/Cisplatin in Small-Cell Urothelial Cancer - SIEFKER-RADTKE, Arlene O; KAMAT, Ashish M; BARTON GROSSMAN, H; WILLIAMS, Dallas L; WEI QIAO; THALL, Peter F; DINNEY, Colin P; MILLIKAN, Randall E (Journal of clinical oncology, 2009)
Currently, treatment recommendations for small-cell urothelial cancer (SCUC) are based on anecdotal case reports and small retrospective series. We now report results from the first phase II clinical trial developed exclusively for SCUC, to our knowledge. From 2001 to 2006, 30 patients with SCUC provided consent and were treated with alternating doublet chemotherapy. Patients with surgically resectable disease (< or = cT4aN0M0) received a total of four cycles of neoadjuvant chemotherapy, whereas those with unresectable disease (> or = cT4b, N+, or M+) received two cycles beyond maximal response. Eighteen patients with surgically resectable SCUC received neoadjuvant treatment with a median overall survival (OS) of 58 months; 13 of these patients remain alive and cancer free. For patients with cT2N0M0 SCUC, the 5-year OS rate is 80%; only one of four patients with cT3b-4aN0M0 remains alive (median OS, 37.8 months). For 12 patients with unresectable or metastatic SCUC, the median OS was 13.3 months. Chemotherapy was well tolerated, with transfusion, neutropenic fever, and infection remaining the most frequent grade 3 and 4 toxicities. There was only one postsurgical death. Brain metastases were strongly associated with more advanced-stage disease, developing in eight of 16 patients with either bulky tumors (> or = cT3b) or metastatic disease (P = .004). These clinical trial results are consistent with previously reported retrospective data demonstrating long-term survival with four cycles of neoadjuvant chemotherapy for surgically resectable SCUC. Once metastases develop, the prognosis remains poor. The strong positive association between disease stage and brain metastases highlights a patient subset that may potentially benefit from prophylactic cranial irradiation.